Fulminant Infective Endocarditis Due to Kingella Kingae and Several Complications in a 6-Year-Old Girl: A Case Report - Joye, Raphael; Ceroni, Dimitri; Beghetti, Maurice; Aggoun, Yacine; Sologashvili, Tornike (Frontiers in Pediatrics, 2021)
Abstract Kingella kingae is a gram-negative coccobacillus that belongs in the HACEK group (Haemophilus species, Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens and Kingella species) and is a common oropharyngeal colonizer in young healthy children. Osteoarticular infection are the most commonly reported Kingella kingae invasive infections in children and usually show a mild clinical picture. However, it is also related to severe invasive infections, especially infective endocarditis, with a high rate of complications. We report the case of a 6-year-old girl, with no past medical history, that presented with a fulminant infective endocarditis due to Kingella kingae. She underwent emergency venoarterial extracorporeal membrane oxygenation support followed by cardiac surgery and was then treated by ceftriaxone for 4 weeks as recommanded by the American Heart Association. The postoperative course was marked by the occurrence of cerebral ischemic stroke consistent with septic embolism. The patient also presented a paraaortic pseudoaneurysm that required a surgical revision with good postoperative result. This case illustrates a fulminant presentation of a Kingella kingae infective endocarditis responsible for two major complications. We also report our experience with valvular preservative surgery, which allowed to preserve valvular function and growth capacity.